Design of a multivariable neural controller for control of a nonlinear MIMO plant - Bańka, Stanisław; Dworak, Paweł; Jaroszewski, Krzysztof (Zielona Góra: Uniwersytet Zielonogórski)
The paper presents the training problem of a set of neural nets to obtain a (gain-scheduling, adaptive) multivariable neural controller for control of a nonlinear MIMO dynamic process represented by a mathematical model of Low-Frequency (LF) motions of a drillship over the drilling point at the sea bottom. The designed neural controller contains a set of neural nets that determine values of its parameters chosen on the basis of two measured auxiliary signals.
Keywords: MIMO multivariable control systems; nonlinear systems; neural control